Smart power consumption in energy digital economy: A perspective of the value co-creation mechanism - Shuyi, Zhang; Pingkuo, Liu; Chen, Zhang; Quansheng, Shi (Frontiers in Energy Research, 2023)
Residential load is one of the important components of the seasonal peak load of the power grid, and it is increasing each year, with a huge demand response potential. With the development of the energy digital economy, the demand response of the new power system shows the characteristics of multi-stakeholder participation. The development mode based on the value co-creation has become a prominent support for market-oriented reform, and the need for the promotion of smart electricity use is increasingly prominent. In order to realize the in-depth exploration of residents’ demand response potential and the sustainable development of “value co-creation” of smart electricity consumption with the participation of multi-stakeholders, this study adopts both the social network analysis method and the counterfactual analysis approach to reveal the general characteristics of agents promoting the residents to participate in the value co-creation of smart electricity positively. The results show that 1) for social network, both the absolute resource advantage and the structural hole have obvious positive guidance on the agent; however, the incentive effect of the relative resource advantage is not significant; 2) for individual nodes , the role positioning of each agent has obvious guiding function for realizing the value co-creation; and 3) for interrelationship among main agents, the functional relationship has a significant degree of interdependence.